Eksplorasi Etnomatematika pada Kerajinan Maghana Penda di Kampung Kalembu Kaha Kecamatan Kota Tambolaka Sumba Barat Daya - Bota, Mariana Ra; Lede, Yulius Keremata; Making, Samuel Rex Mulyadi; Lubur, Dorothea Novia Ludo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to explore ethnomathematics in maghana penda crafts in Kalembu Kaha Village, Tambolaka City District, Southwest Sumba. Ethnomathematics is a science used to understand how mathematics is adapted from a culture and serves to express the relationship between culture and mathematics. This type of research is qualitative research with an ethnographic approach. The subject of the study is the place where the data for the research variables are obtained. Data analysis techniques in this study were carried out during and after data collection. The results of the research show that several pandan woven crafts in Kalembu Kaha village contain mathematical concepts such as rectangles, rhombuses, triangles and cylinders which can be used in contextual mathematics learning at school.